Event-based cultural life scripts and the effect of personal experiences - Güllü, Büşra Nur. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
The cultural life script theory states that there are shared expectations among the members of the same culture regarding the important events in a prototypical life course, and timing and order of them. These events were defined by the theory as extended events with episodes nested in them. To understand if these episodes/subevents are also shared within the same culture that forms event-based life scripts, the present study investigated the expectations regarding a typical university, marriage, and retirement life for Turkish culture. Participants’ personal experience regarding these expectations were also collected. The results revealed scripts for all three events that were generally in line with the cultural life script theory. The temporal distribution of reported subevents showed a bump for certain age-periods. These bumps were examined for their resemblance to the reminiscence bump. Additionally, the effect of personal experience on the scripts were examined both in event and subevent levels when sample size was enough. The majority of these comparisons did not yield any significant difference between participants who had experience and participant who did not have. Still, several differences that hinted on the effect of personal experiences existed. The results were discussed in terms of considering event-based scripts as semantic knowledge.
Keywords: Intellectual life.